Single crystal growth of water-soluble metal complexes with the help of the nano-crystallization method. Issue 28 (2nd July 2020) - Alvarez, Ricardo; Nievergelt, Philipp P.; Slyshkina, Ekaterina; Müller, Peter; Alberto, Roger; Spingler, Bernhard
Abstract : Let pipetting robots set up nano crystallization trials of water-soluble metal complexes in order to obtain single crystals! Abstract : The Nano-Crystallization method has been extensively tested for the growth of single crystals of cationic coordination compounds, which are soluble in water. All three studied, diverse metal complexes could be crystallized with the help of pipetting robots commonly used for the crystallization of proteins and the anion small molecule screen. It was furthermore possible to obtain for each positively charged complex several structures with different anions. In one case, together with literature data, a total of six salts with different anions could be assembled, which allowed an investigation of the influence of the counterions on the inter-cation metal-to-metal distance. The Nano-Crystallization method can be recommended for the single crystal growth of cationic coordination complexes, which are stable in water and have an aqueous solubility of at least 2 mM. This is the first publication dedicated solely to the single crystal growth of coordination complexes.